2023
DOI: 10.1021/acsami.3c09219
|View full text |Cite
|
Sign up to set email alerts
|

Co-assembled Supramolecular Hydrogel of Salvianolic Acid B and a Phosphopeptide for Enhanced Wound Healing

Xiaojing Huang,
Tingting Li,
Xingyue Jiang
et al.

Abstract: Supramolecular natural product gels (NPGs) have emerged as promising biomaterials for scalable and adjustable drug delivery systems. These gels possess biocompatibility, biodegradability, and the ability to mimic the extracellular matrix. Salvianolic acid B (SAB), derived from Salvia miltiorrhiza, a Chinese medicinal plant, exhibits various beneficial properties such as antioxidant, antifibrotic, and angiogenic effects. In our research, we serendipitously discovered that the co-assembly of SAB and a soluble ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Compared to free drugs, these hydrogels more readily enter cells, subsequently achieving anti-neuroinflammatory therapy by inhibiting the Toll-like receptor 4/nuclear factor-κB signaling pathway [ 162 ]. In another study, salvianolic acid B and NapFFKYp could form a spontaneous hydrogel that promoted wound healing [ 163 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to free drugs, these hydrogels more readily enter cells, subsequently achieving anti-neuroinflammatory therapy by inhibiting the Toll-like receptor 4/nuclear factor-κB signaling pathway [ 162 ]. In another study, salvianolic acid B and NapFFKYp could form a spontaneous hydrogel that promoted wound healing [ 163 ].…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al co-assembled salvianolic acid B (SAB) and a soluble phosphopeptide to design a robust and adhesive non-covalently crosslinked hydrogel called 1&SAB. 147 This hydrogel possesses antioxidant properties, enhances cell migration, accelerates angiogenesis, and prolongs the residence time of therapeutic agents on skin wound surfaces, thereby promoting wound healing. Xing et al designed a chiral non-covalently crosslinked hydrogel dressing (HA-LM2-RMR) composed of l-phenylalanine and cationic hexapeptide co-assembled helical nanofibers cross-linked with hyaluronic acid via hydrogen bonding.…”
Section: Biomedical Applications Of Stimuli-responsive Peptide Hydrogelsmentioning
confidence: 99%
“…Salvianolic acid B (SAB) has been widely used for neuroprotection and recovery treatment after brain injury due to its anti-inflammatory, anti-oxidation, and angiogenesis effects [34][35][36]. Our previous studies have shown that the combination of SAB in HA hydrogel can promote wound healing via anti-inflammatory and pro-angiogenic effects [37][38][39]. In addition, SAB-loaded hydrogel can effectively improve blood supply and inhibit extracellular matrix degradation after myocardial infarction [40].…”
Section: Introductionmentioning
confidence: 99%